Warfarin-Induced Skin Necrosis Following Heparin-Induced Thrombocytopenia. Issue 1 (1st January 2016) - Fawaz, Bilal; Candelario, Nicole M.; Rochet, Nicole; Tran, Connie; Brau, Cristina
Abstract : Anticoagulants, such as heparin and warfarin, are commonly used in the treatment and prevention of thromboembolic events. The risk of developing warfarin-induced skin necrosis (WISN) with warfarin is reported to be <1%. However, the risk of WISN may be increased with the initiation of warfarin in the setting of heparin-induced thrombocytopenia and thrombosis syndrome (HITT). WISN can lead to catastrophic tissue necrosis requiring amputations and mass debridement. This report describes a case of WISN following HITT and discusses the appropriate medical management of patients with HITT to avoid secondary WISN.